Thermal buoyancy driven canyon airflows inside the compact urban blocks saturated with very weak synoptic wind: Plume merging mechanism. (March 2018) - Mei, Shuo-Jun; Hu, Jiang-Tao; Liu, Di; Zhao, Fu-Yun; Li, Yuguo; Wang, Han-Qing
Abstract: During the sunny days with very weak wind, thermal buoyancy forces will play a crucial role in the airflow and urban thermal environment. The merging effect of urban building plumes is particularly investigated by the use of unsteady Reynolds-averaged Navier Stokes (URANS) methodology. After testing against benchmark theoretical results, the SST k - ω model showing better performance in capturing the near wall processes and it was adopted to simulate the urban turbulent flows. The airflow patterns and temperature fields are analyzed for seven urban sizes ranging from 3 to 10 rows of buildings and six aspect ratios ranging from 0.5 to 3.0. The merging of thermal plumes induces a horizontal convergence flow, resulting in stagnant region at the urban center. A typical urban heat island temperature distribution with a peak value at the urban center is then found. Additionally, with the increase of urban size, the averaged velocity with the canyon decreases and averaged temperature increases. The average velocity within the street canyon decreases monotonously and the vortices number increases with the aspect ratio (building height H to the street width W ). The average temperature also increases with aspect ratio, except when the aspect ratio increases from 2.0 to 2.5, where the flow structure within the street canyon changes from a three vortices structure into a four vortices structure. This research could provide a new idea about how urban heat island is formed and the relation between its intensity with urban size and geometry. Highlights: The urban building plumes merging is numerically investigated. UHI temperature distribution is observed under very weak synoptic wind. Hot air is trapped within urban canyons due to plume merging and vortices. Temperature level in the city centre increases monotonously with urban size. Thermal environment within street canyons is directly related to the flow structure.